Subjective feelings of mental fatigue differs between competitive phases in semi-professional soccer - Diaz-Garcia, J.; Rubio-Morales, A.; López-Gajardo, M. A.; Ponce-Bordón, J. C.; García-Calvo, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Soccer game scenarios imply vigilance, decisions making, emotions or constantly processing information causing mental fatigue in soccer players (Coutts, 2016). Mental fatigue may impair soccer physical and technical-tactical performance (Badin et al., 2016; Coutinho et al., 2017). Therefore, controlling and limiting the presence of mental fatigue may be important for enhancing soccer performance. The present study aimed to check the influence of play a play-offs phase on the mental fatigue reported by semi-professional soccer. 53 players (Mage=24.59 years) for two semi-professional teams participated during the 2020/21 season. Mental fatigue was quantified with a Visual Analogue Scale during four trainings per week (Monday=MD+1, Wednesdey=MD-4, Thursday=MD-3 and Saturday=MD-1), with a competitive match on Sunday. The total duration of the study was 10-weeks (five dates of regular season - five dates of play-offs). A Linear Mixel Model was performed with R-studio, using the competitive phase as independent variable. The results showed that the mental fatigue reported by players was significantly higher during the play-offs phase that during the regular season. The play-offs phase is played by the best teams of a competition whereplayers usually have monetary recompenses by achieve the objectives or possibilities to sign better contracts the next season. Despite we have not the specific data to confirm this, the results suggest that the play-offs phase implies emotional demands that may increase the mental fatigue reported by players. Then, in agreement with Van Cutsem and Marcora (2021) we recommended coaches the possibility to use recovery strategies for mental fatigue during the play-offs phase (specially nearly the match day) and to avoid the presence of mentally fatiguing tasks nearly competitions.